Evaluation of robots that signals a pedestrian using face orientation based on analysis of velocity vector fluctuation in moving trajectories. (17th October 2020) - Yamashita, Shohei; Kurihara, Tomohiro; Ikeda, Tetsushi; Shinozawa, Kazuhiko; Iwaki, Satoshi
Abstract : In this paper, we focus on mobile robots' behavior that people around them feel comfortable. The subjective comfort of pedestrians is usually evaluated by a questionnaire, but the high cost of assessment makes it difficult to evaluate in various situations. Towards robot control based on objective measurements of pedestrians, this paper proposes an index to evaluate the ease of walking based on objective measurements of a pedestrian's trajectory. To verify the index, we introduce a mobile robot that (1) signals it has noticed a pedestrian in front of it by moving its head upward, then (2) signals the direction of future movement by turning its head. Then the robot's behavior was evaluated by subjective impressions and objective evaluation index. We examined the relationship between subjective impressions and the objective evaluation index. GRAPHICAL ABSTRACT: UF0001